THE FUTURE OF HR IN HOSPITALITY: TECHNOLOGY-DRIVEN HRM PRACTICES - Mandić, Dušan; Ječmenica, Dejan; Stanišić, Nataša (The European Journal of Applied Economics, 2025)
HR has a crucial role in creating and implementing plans to attract, retain, and motivate staff in the highly competitive hotel industry. HR must use creative strategies to boost employee engagement and productivity as the sector faces labor challenges like high turnover rates and a lack of skilled workers. By optimizing hiring procedures, increasing retention, and personalizing career progression, technology-based HR strategies—such as AI-enhanced recruitment, gamified training, predictive analytics, and digital wellness programs—are revolutionizing workforce management.The integration of virtual reality (VR) onboarding and AI-driven performance tracking enhances training efficiency, while predictive analytics enables HR professionals to identify employees at risk of leaving and implement targeted retention strategies. However, despite these benefits, challenges such as data privacy concerns, employee resistance to digital adoption, and high initial costs must be managed.Predictive analytics enables HR professionals to identify potential departing employees and implement targeted retention strategies, while virtual reality (VR) onboarding and AI-powered performance monitoring enhance the efficacy of training. However, despite these benefits, there are still challenges that must be resolved, such as data privacy concerns, employee resistance to digital adoption, and high initial expenses. Through the effective integration of data-driven technologies and human-centered approaches, hotels may assure long-term success in a rapidly evolving business, increase employee productivity, and improve guest satisfaction.
Keywords: Hotel, Employees, HR, Productivity, Innovations